Взаимосвязь показателей методики PARI с показателями детско-родительских отношений в семьях с тяжелобольным ребенком - Fedorenko M. V., Nabieva R. I. (Innovative technologis in science and education, 2016)
The paper presents the results of diagnostics of parent-child relationships in families with a child with acute lymphoblastic leukemia. Correlation analysis showed that there was significantly strong relationship between indicators PARI techniques designed to study the relationship of mothers to different sides of family life and performance diagnostics of children with acute lymphoblastic leukemia.
Keywords: детско-родительские отношения; семейные роли; методика PARI; острый лимфобластный лейкоз; the PARI technique; acute lymphoblastic leukemia; parent-child relationship; family roles